2019
DOI: 10.3390/nano9101378
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein- and EGFR-Antibody Conjugated Silica Nanoparticles for Enhancement of Real-time Tumor Border Definition Using Confocal Laser Endomicroscopy in Squamous Cell Carcinoma of the Head and Neck

Abstract: Intraoperative definition of tumor free resection margins in head and neck cancer is challenging. In the current proof-of-principle study we evaluated a novel silica nanoparticle-based agent for its potential use as contrast enhancer. We synthesized silica nanoparticles with an average size of 45 nm and modified these particles with the fluorescence stain fluorescein isocyanate (FITC) for particle detection and with epidermal growth factor receptor (EGFR)-targeting antibodies for enhanced tumor specificity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
(22 reference statements)
0
15
0
2
Order By: Relevance
“…In addition, it was reported that MSNs may reduce the amounts of endogenous ROS leading to enhanced malignant melanoma growth . Also, accumulation of MSNs in normal body organs, specially the liver and spleen is an issue that needs to be addressed before further translation of MSNs into clinical practice …”
Section: Applications Of Msnsmentioning
confidence: 99%
“…In addition, it was reported that MSNs may reduce the amounts of endogenous ROS leading to enhanced malignant melanoma growth . Also, accumulation of MSNs in normal body organs, specially the liver and spleen is an issue that needs to be addressed before further translation of MSNs into clinical practice …”
Section: Applications Of Msnsmentioning
confidence: 99%
“…In any nanocarrier system designed for in vivo applications, the toxicity of the nanoparticles is one of critical issues that needs to be extensively investigated. Although many reports from the literature showed that the applications of MSN‐based nanocarriers possess low or negligible in vivo systemic toxicity profile, it was revealed in a review paper reported by Brinker et al . that there is a consensus about the undesired toxicity that might be associated with the application of MSN‐based nanocarriers is mainly due to the availability of highly reactive surface silanol (SiOH) functional groups.…”
Section: Various Types Of Nanoparticles For Therapeutic Nanoreactors mentioning
confidence: 99%
“…Silica nanoparticle has a wild range of applications in bio‐nanotechnology due to their physical, chemical, and optical properties such as chemical modification diversity, biocompatibility, optical transparency, low toxicity, and particle‐size tunability [14] . Silica nanoparticles are mostly used in drug delivery, [15] biosensors, [16] and bio‐imaging [17] . Mesoporous silica nanoparticles (MSNPs) own a unique structure with an adjustable pore and particle size, leading to a large specific surface area which can be easily functionalized.…”
Section: Introductionmentioning
confidence: 99%